SYSTEMATIZATION OF NURSING ASSISTANCE TO FIBRODYSPLASIA CARRIER PROGRESSIVE OSSIFICANS - Salviano de Vasconcelos, Izabelle; Carolina Salustino dos Santos, Maria; Izaltemberg Rosenstock, Karelline; de Oliveira Souza, Eclésia; Casado de Freitas Silva, Rosany; Costa Soares Silva, Talita; da Silva Caldas, Walissioneide; de Araújo Evangelista, Wanessa; Thallyta Alexandre de Pontes, Arunna (Health and Society, 2022)
Aiming at the importance of the nurse in the different directions and health care, studies point out the daily challenge of nursing professionals in relation to the importance of considering genetic aspects and in the care of patients with rare genetic diseases, such as Progressive Ossificans Fibrodysplasia (FOP) which is a rare genetic disease that stimulates the formation of bones inside the muscles, tendons, ligaments and other connective tissues progressively restricting movements, causing too much nursing care. This study aims to broaden the nurses’ knowledge about Fibrodysplasia Ossificante Progressiva (FOP), in addition to reporting the main difficulties in the care of patients with FOP; and discussing the importance of appropriate care for the carrier of this rare genetic disease by drawing up a qualified care plan. It is a research of the type bibliographic research of explanatory-descriptive character with qualitative approach, based on bibliographical reviews. According to the material analyzed, it is observed the importance of nurses’ knowledge regarding the disease and its respective treatments and types of care, and for this it is necessary that they have an adequate basis from a knowledge directed through courses, qualifications, lectures and qualified theoretical background. Consequently, in order to perform good care, nurses should guide their team about the best way to assist the patient, making it clear that there is a great challenge when it comes to the unusual, in order to show that it is possible to guarantee correct assistance for these patients.